Jitter as the main affecting factor in the performance of PDAs - Rodríguez Guillén, Reinier; Ferrer Riesgo, Carlos A. (My University, 2019)
Jitter measurement is a frequent task in the acoustic analysis of pathological voices, and it relies in the previous determination of glottal pulse boundaries. The Praat software system has become a widely used tool to obtain both the pulse boundaries and the jitter measures. However, results provided by Praat can be misleading if the internal implementations of the procedures used to obtain the pulse boundaries are ignored. This paper addresses the influence of some of these settings in the ability of Praat to obtain these markers. Simulations are conducted to evaluate the effects of different types of periodicity perturbations (jitter, shimmer, noise, and their combination) and their levels on the resulting performance.
Keywords: jitter, shimmer, noise, Praat, PDAs, pathological voice.